Análisis del fenómeno de lavado de lodos en tres tipos de reactores anaerobios de flujo intermitente tratando agua de rastro - Alanís Ramírez, David (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The slaughterhouses work typically only a few hours per day generating intermittent wastewater flow. This situation presents an issue when choosing a treatment system because the conventional design of these systems is performed considering continuous and not intermittent flow. This work presents an analysis of sludge washout phenomenon in anaerobic reactors UASB, ABR and ASBR, operating with intermittent flow. The experiment was conducted in three anaerobic reactors of 14 liters to laboratory scale, which were fed Monday to Friday during periods of 6 hours and 18 hours without feeding. This was done to simulate the conditions presented by the wastewater flow in a slaughterhouse. The reactors were inoculated with 4.25 liters of granular sludge with a concentration of 33 g/l of VSS, being worked at a temperature of 32 ° C. The pH of the influent was controlled at a value of 7.5 and the HRT was 2 days. The influent COD was controlled at a value close to 5000 mg/l for the first stage of the experiment and the order of 10,000 mg/l for a second stage. Biogas production was around 0.4 liters biogas/gCODremoved. The sludge washout phenomenon was analyzed by evaluation of solids loss for 6 weeks for each reactor. The results obtained were as follows: the amount of sludge in the UASB reactor decreased 11.5% and 8%, while the decrease in the ABR was 60% and 75% for stage 1 and 2 respectively. ASBR type reactor showed an increase of 5% in the amount of sludge for stage 1, however, during stage 2 suffered decrease of 68%. The condition of sludge washout occasioned a reduction in the biomass inward the reactors which caused decrease in efficiency of treatment and biogas production.

Los rastros trabajan por lo general solo algunas horas del día generando un flujo intermitente de agua residual. Esta situación presenta un inconveniente al elegir un sistema de tratamiento ya que el diseño convencional de estos sistemas se realiza considerando un flujo continuo y no intermitente. En este trabajo se presenta un análisis del fenómeno de lavado de lodos en los reactores anaerobios UASB, ABR y ASBR, operando con flujo intermitente. La experimentación se realizó en tres reactores anaerobios a escala laboratorio de 14 litros de capacidad, los cuales se alimentaron de lunes a viernes en periodos de 6 horas y dejándose sin alimentación 18 horas. Esto con la finalidad de simular las condiciones que presenta el flujo de agua residual en un rastro. Los reactores se inocularon con 4.25 litros de lodo granular con una concentración de 33 g/l de SSV, trabajándose a una temperatura de 32°C. El pH del influente se controló a un valor de 7.5 y el TRH fue de 2 días. La DQO del influente se controló en un valor cercano a 5000 mg/l para la primera etapa del experimento y del orden de 10000 mg/l para una segunda etapa. La producción de biogás fue del orden de 0.4 litros de biogás/gDQOremovida. El fenómeno de lavado de lodos se analizó evaluando la pérdida de sólidos por un periodo de 6 semanas en cada reactor. Los resultados obtenidos fueron los siguientes: en el reactor UASB la disminución de la cantidad de lodos fue de 11.5 % y 8% mientras que para el ABR fue de 60% y 75% para la etapa 1 y 2 respectivamente.
Facultad de Biología. Facultad de Ingeniería Civil. Facultad de Ingeniería Química. Maestría en Ciencias en Ingeniería Ambiental
Keywords: info:eu-repo/classification/cti/7; FIQ-M-2014-1962; Rastro; AMR; ASBR; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4705